STUDI PEMANFAATAN LIMBAH KULIT DURIAN (Durio Zibethinus Murr) SEBAGAI BAHAN BAKAR PADAT ALTERNATIF DENGAN TEKNOLOGI HYDROTHERMAL - Trihastanto Hadi Nugraha; Nugroho Agung Pambudi; Ranto Ranto (Nozel : Jurnal Pendididikan Teknik Mesin, 2019)
The purpose of the study are analyzed the potential energy of durian peels as an ingredient of solid fuel use the conversion of biomass hydrothermal technology. This study used an experimental method with hydrothermal treatment. Variations used in this method are temperature variations of 180°C, 200°C, and 220°C with variations in holding times of 30 minutes and 60 minutes. To determine the fuel content of durian peels, heating values and proximate analysis were carried out to determine water content, ash content, volatile content, and carbon content. The test result showed that durian peels waste is suitable to be used as an alternative fuel that is suitable for lignite coal fuel. In testing, the highest calorific value is 4515.52 kal / gram which was equivalent to the calorific value of lignite coal (3500 - 4611 cal / gram) according to the American Standard Testing and Mineral (ASTM).